PENGARUH IMPLEMENTASI KEBIJAKAN KURIKULUM TERHADAP MANAJEMEN PEMBELAJARAN DALAM UPAYA MEWUJUDKAN CAPAIAN PEMBELAJARAN SISWA - Hazim, Muhammad; Ulumudin, Aceng; Tajudin Zuhri, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of suboptimal student learning achievement at Madrasah Aliyah Negeri (MAN) 1 Garut, characterized by fluctuations in academic grades and less than maximal mastery of student competencies according to expected standards. This condition indicates that the implementation of curriculum policies has not been fully effectively integrated with classroom learning management. The study aims to analyze the influence of curriculum policy implementation on learning management, the influence of learning management on learning achievement, and the direct influence of curriculum policy on student learning achievement. The research method employed is a quantitative approach with an explanatory survey method. The population consists of all teachers at MAN 1 Garut using a saturated sample technique (total sampling) of 76 respondents. Data were collected through Likert-scale questionnaires and analyzed using Path Analysis techniques with SPSS software. The results show that curriculum policy implementation has a positive and significant effect on learning management with a contribution of 37.5%. Learning management is proven to have a positive and significant effect on student learning achievement. Simultaneously, curriculum policy implementation and learning management contribute 53.9% to student learning achievement. Based on these findings, it can be concluded that the synergy between adaptive curriculum policies and professional learning governance is crucial for improving student learning outcomes holistically.